The survivin/XIAP suppressant YM155 impairs clonal growth and induces apoptosis in JAK2V617F cells - Jorge Antonio Elias Godoy Carlos; Keli Lima; Eduardo Magalhães Rego; Leticia Veras Costa-Lotufo; João Agostinho Machado-Neto (Hematology, Transfusion and Cell Therapy, 2024)
The central role of the control of apoptosis in the pathophysiology of Philadelphia chromosome-negative myeloproliferative neoplasms has recently been reinforced in genetic and pharmacological studies. The inhibitor of apoptosis protein family has eight members and plays an important role in apoptosis, with the most studied being survivin (BIRC5) and X-linked inhibitor of apoptosis (XIAP). YM155 is a small molecule with antineoplastic potential that has been described as a suppressant of survivin and XIAP. In the present study, BIRC5 expression was significantly increased in primary myelofibrosis patients compared to healthy donors. On the other hand, XIAP expression was reduced in myeloproliferative neoplasms patients. In JAK2V617F cells, YM155 reduces cell viability and autonomous clonal growth and induces apoptosis, cell cycle arrest, and autophagy. HEL cells that show greater malignancy are more sensitive to the drug than SET2 cells. In the molecular scenario, YM155 modulates apoptosis-, cell cycle-, DNA damage- and autophagy-related genes. Protein expression analysis corroborates the observed cellular phenotype and exploratory gene expression findings. In summary, our results indicate that survivin/BIRC5 and XIAP are differently expressed in myeloproliferative neoplasms and YM155 has multiple antineoplastic effects on JAK2V617F cells suggesting that inhibitor of apoptosis proteins may be a target for pharmacological interventions in the treatment of these diseases.